Neljän luokanopettajan ajatuksia historiataitojen asemasta omassa opetuksessaan - Virrankari, Daria (Helsingfors universitet, 2016)
Teaching historical thinking in elementary school has been part of the curriculum since 1994. In this study historical thinking is seen as in the current curriculum (OPS 2004) as source skills, understanding time, cause and effect and historical empathy. Although teaching historical thinking has been part of the curriculum for 20 years, its teaching in elementary school has been scarce. The research problem is why historical thinking is not taught as it stands in the curriculum. In this study I survey four class teacher's thoughts about historical thinking in their teaching and how the teachers' vision of history as a school subject affects their teaching of historical thinking. I also examine how teaching materials used by teachers affect the teaching of historical thinking and compare the teachers' visions to research literature on the subject. Study was executed as a semi-structured thematic interview. During the spring of 2015 I interviewed four history teaching class teachers in Southern and Northern Finland. Interviewees were selected so that they would differ from one another for example by their background, teaching experience and alma mater. Interviews were recorded with the acceptance of the interviewees and transcribed for analysis. The data was analyzed using textual analysis and by comparing it to existing surveys. The study shows that the teachers' vision of history is outdated; ergo it is not in line with the targets set by the current curriculum. In the teachers' thoughts knowing history was seen as remembering important things and explaining the present through the past. The study also suggests that the teachers are not fully aware what is meant by historical thinking. It revealed that the teaching of history, at least in the eyes of the four teachers surveyed, leans a lot on history schoolbooks, which also respond badly to aims set by the curriculum. Historiataitojen painottaminen on ollut osa Perusopetuksen opetussuunnitelmaa jo vuoden 1994 opetussuunnitelmasta lähtien. Historiataidoilla ...